An Innovative Academic/Practice Partnership to Support Nursing Workforce Needs and Student Clinical Education. (February 2023) - Hahn, Judith; Resha, Cheryl-Ann; Beauvais, Audrey; Beckman, Beth; Forte, Pamela; Rebeschi, Lisa M.; Snyder, Marianne
ABSTRACT: Innovation is needed to solve nursing workforce issues during times of crisis. A collaborative effort between a hospital system and several universities resulted in the Bridge to Professional Practice Program that was implemented during a period of high patient volume and nursing student downtime. The program provided support for staffing needs and clinical hours to promote readiness for practice for students. The program evaluation outcomes and recommendations for improvement are addressed.